Raul Proença: há futuro no eterno retorno? - Natário, Maria Celeste (2017)
Based on the thinking of the Portuguese philosopher Raul Proença and specifically from his essay, The philosophy of Epicurus and the heroic conception of life, published in 1922, we will reflect on some essential features of his vision about the being and the future-time, which naturally results in a dialogue with the German philosopher Nietzsche about the Eternal Return.